1997
DOI: 10.1002/bbpc.19971011212
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of pyrite thermal decomposition

Abstract: Pyrite (FeS2) decomposition in He, N2, CO2‐CO‐SO2, O2‐CO2 and H2S‐H2 gas mixtures was studied from 400–590°C using optical microscopy, X‐ray diffraction, electron microprobe analyses, and gas chromatography. The rate constants were determined from the weight loss and the thickness change of pyrite in reacted samples. The temperature dependent composition of the product, pyrrhotite (Fe1‐xS), was measured by electron microprobe analysis and X‐ray diffraction. Pyrite decomposition to pyrrhotite and sulfur vapor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…However, pyrite decomposition experiments showed that not only would the nature of released sulfur allotropes affect the overall energy distribution of the decomposition process, the efficiency of vaporization of liquid sulfur produced would also be critical (Hong and Fegley 1997). The vesicular pyrrhotite textures and correlation of vesicle size with increasing Fe-oxide formation suggest that efficient pathways for loss of sulfur existed during flash-heating of sulfur IDPs described here.…”
Section: Dynamic Pyrometamorphism Temperatures and Idp Sourcesmentioning
confidence: 85%
See 3 more Smart Citations
“…However, pyrite decomposition experiments showed that not only would the nature of released sulfur allotropes affect the overall energy distribution of the decomposition process, the efficiency of vaporization of liquid sulfur produced would also be critical (Hong and Fegley 1997). The vesicular pyrrhotite textures and correlation of vesicle size with increasing Fe-oxide formation suggest that efficient pathways for loss of sulfur existed during flash-heating of sulfur IDPs described here.…”
Section: Dynamic Pyrometamorphism Temperatures and Idp Sourcesmentioning
confidence: 85%
“…9). Should liquid sulfur vaporization have been fast enough, pyrrhotite decomposition might have followed the one-step release of a S 2 molecule as was experimentally verified by Hong and Fegley (1997) during pyrite decomposition.…”
Section: Sulfide Oxidation and Sulfur Lossmentioning
confidence: 87%
See 2 more Smart Citations
“…sulfur gases in the Venus sulfur cycle (Fegley and Treiman 1992, Fegley et al 1995b, Hong and Fegley 1997, 1998. Thus, determination of the nature and the abundance of Febearing minerals in rocks and soil will provide important information about atmospheric weathering processes.…”
Section: Introductionmentioning
confidence: 99%